Disaster, disruption and disability- a multi-center parental survey of the mental health impact of COVID-19 pandemic on children with and without disabilities in India - Sengupta, Koyeli; McGowan, Jo Chopra; Desouza, Nandita; Nagesh, Shubha; Goel, Richa; Sinha, Namya (International Journal of Contemporary Pediatrics, 2022)
Background: The COVID-19 pandemic has impacted the pediatric population worldwide, with Children with developmental disabilities (CwDD) being particularly vulnerable. Data on the magnitude of the impact of the pandemic on children in India, particularly CwDD is much needed. The aim of the study was to explore parental perceptions of the impact of the COVID lockdown on daily behaviors and mental health outcomes of Typically developing children (TDC) compared to CwDD. Methods: A cross-sectional survey was conducted on 708 parents of CwDD and TDC (age 2-18 years) in three centers in northern and western India, using an adapted version of the CoRonavIruS health and Impact Survey (CRISIS) questionnaire. Descriptive statistics, 2-sample t-tests, and linear regression models were analyzed. Results: Opportunities to step out reduced equally for both CwDD and TDC (p>0.05), while social isolation was perceived more negatively (p<0.001) by TDC. Family’s exposure to COVID was significantly lower (p=0.01) for CwDD, while financial stress due to COVID-19 was reported by both groups (p>0.05). Although composite scores for mental health during the pandemic were not significantly different between CwDD and TDC, parents reported worsening of children’s mental health outcomes with 18.29% CwDD and 25.48% TDC as sad, 28.99% CwDD, and 32.03% TDC as anxious, 56.33% CwDD and 51.78% TDC as irritable and 40.47% CwDD and 38.08% TDC as distracted. Conclusions: As per parental perceptions, mental health outcomes of CwDD and TDC have deteriorated similarly during the lockdown. However, the implications may be more severe for CwDD whose levels of independence, opportunities for participation, and mental health status were lower even pre-COVID.